1993
DOI: 10.1016/s0092-8240(05)80189-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune network behavior—II. From oscillations to chaos and stationary states

Abstract: Two types of behavior have been previously reported in models of immune networks. The typical behavior of simple models, which involve B cells only, is stationary behavior involving several steady states. Finite amplitude perturbations may cause the model to switch between different equilibria. The typical behavior of more realistic models, which involve both B cells and antibody, consists of autonomous oscillations and/or chaos. While stationary behavior leads to easy interpretations in terms of idiotypic mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…If in the past, mathematical models in immunology were limited to a few groups, such as the Los Alamos T‐10 group led by Perelson and his trainees (8, 15, 82, 131–134) and Nowak (23, 135–140), there are now current practices in all fields of immunology. Mathematical models that were once a minor branch based on theoretical considerations are now associated with most domains of molecular immunology and are often driven by precise experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…If in the past, mathematical models in immunology were limited to a few groups, such as the Los Alamos T‐10 group led by Perelson and his trainees (8, 15, 82, 131–134) and Nowak (23, 135–140), there are now current practices in all fields of immunology. Mathematical models that were once a minor branch based on theoretical considerations are now associated with most domains of molecular immunology and are often driven by precise experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown that on the level of cells nonlinear dynamics can also be observed [24,[40][41][42][43][44][45][46][47][48]. Up to now, there is only few information concerning the probable relevance of complex cell reactions to trauma and shock responses such as chemotaxis, leukocyte accumulation, and granulocyte migration [44,46].…”
Section: Level Of Cellsmentioning
confidence: 99%
“…Am J Physiol 1995 [12] Decrease of the complexity of arterial blood pressure control in conscious dogs by baroreceptor denervation Int J Microcirc Clin Exp 1997 [87] Vasomotor activity in microvascular perfusion Immune system Bull Math Biol 1993 [41,45] Nonlinear behavior in B-cell production of antibodies Microbiology Int J Clin Pharmacol Ther 1995 Nonlinear approach for a better understanding [88] of the pharmacokinetics and -dynamics of aminoglycosides matical techniques are phenomenological and attempt to assess the qualitative character of a system's dynamics. Some of the techniques allow short-range predictions but without attempting to provide an understanding of the biological or physical mechanisms that ultimately govern the behavior of the system.…”
Section: Vasomotionmentioning
confidence: 99%